TOXIC EFFECTS OF CHEMICALS ON HUMAN HEALTH DURING EMERGENCY SITUATIONS IN CHEMICAL ENTERPRISES - U. M. Norqulov; D. A. Kurbanova; A. A. Bazarbayev; Yu. B. Mirzaqobilov; Norqulova Lobar Uchqunovna (Zeta Repository, 2023)
This article describes emergency situations, poisoning thresholds, processes that occur in the body under the influence of toxic chemicals and toxins, the spread of toxic chemicals in the body, their excretion and metabolism, the classification of chemicals according to the mechanism of action, and the diagnosis of poisoning. Done.